Morphological and spectroscopic analysis of snow and glacier algae and their parasitic fungi on different glaciers of Svalbard - Marta J. Fiołka (Nature Portfolio, 2021)
Abstract The results show the morphological analyses and spectroscopic studies of snow and glacier algae and their parasitic fungi in Svalbard (High Arctic). Fixed algal cells of two species, Sanguina nivaloides and Ancylonema nordenskioeldii, were imaged using light microscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM). Fluorescence microscopy using Calcofluor white stain supported the observations of parasitic fungi on the algal cells. Images in brightfield microscopy showed chytrid-like fungi penetrating the cells of both algal species. Parasites were found to colonize the cells of A. nordenskioeldii and hypnozygotes of S. nivaloides, while no fungi infected the cyst stages of S. nivaloides. The autofluorescence analysis revealed the ability of S. nivaloides to glow when excited with different wavelengths, while A. nordenskioeldii did not fluoresce. The hypnozygotes of S. nivaloides emitted brighter fluorescence than the cysts, and the most intense luminosity was observed in the UV range. The Fourier-transform infrared spectroscopy (FTIR) and energy-dispersive X-ray spectroscopy (EDS) spectroscopic analysis showed differences in the chemical composition between samples collected from three different sites. Samples dominated by cyst cells were characterized by the presence of an abundant polysaccharide envelope.